Pengaruh Kepemimpinan Kepala Sekolah dan Budaya Kerja terhadap Kinerja Guru SMP Swasta Maitreya Se-Sumatera - Tek Jan (Institut Nalanda, 2024)
This study aimed to examine The influence of the principal's leadership and work culture individually and simultaneously on performance teaching. A total of 86 Private Middle School teachers Maitreya throughout Sumatra participated voluntarily in the study. The study uses quantitative research methods. Analysis of data uses simple partial regression and correlation and multiple correlation. The results of this study show that there is a positive and very significant correlation of the independent variables of Leadership and Cultur Work together to the interest in teaching, whereby the results of the correlation coefficient is ry.12 = 0.774 and the determinant coefficient is r2y.12 = 0.599, meaning the two variables contribute to the interest in performance teaching by 59,9%. That also means there are other factors that influence the interest in Performance teaching as many as 41,1%. The independent variable ‘Leadership’ influence, individually has a very weak positive and significant relationship to the interest in teaching compared to other variables, showed by the correlation coefficient: ry.1 = 0.725 and the determinant coefficient r2y.1 = 0.526. It means the contribution of Self the principal's leadership performance teaching in teacher is 52,6 %. Whereas Culture Work, individually, shows the correlation coefficient is ry.2 = 0.601 and the determinant coefficient r2y.2 = 0.362. It means Culture Work contributes 36,2% to the interest in Performance teaching while 63,8% is contributed by other variables. It also means that Culture Work has a strong positive influence and is very significant to the interest in performance teaching.